Kombinasi Algoritma Brute Force dan Stemming pada Sistem Pencarian Mashdar - Rozzi Kesuma Dinata; Safwandi Safwandi; Novia Hasdyna; Rudi Mahendra (CESS (Journal of Computer Engineering, System and Science), 2020)
In this study Brute Force and Stemming algorithms are combined in the mashdar word search system. The purpose of this study is to facilitate the user in finding the basic words of a word along with its changes based on the review of basic words to mashdar. The data used in this study were obtained from 50 books of Tashrif by Sheikh Hasan bin Ahmad. The results of the study by combining brute force and stemming algorithms in mashdar search with a test sample of 15 words obtained an accuracy value of 78.9%, 86.6% precission, 84.6% recall and 66.6% specificity.